2001
DOI: 10.1080/02673030020015146
|View full text |Cite
|
Sign up to set email alerts
|

Moving or Improving: Housing Adjustment Choice in Kumasi, Ghana

Abstract: This paper examines housing adjustment choice of households in Kumasi, Ghana. When a household is dissatis ed with its housing, it can choose to move elsewhere, improve the current dwelling, or neither. Using data from a 596-household survey collected in 1996, logistic regressions are used to examine the determinants of this choice. Results suggest that housing satisfaction and quality, plus some household characteristics, in uence the choice of undertaking housing adjustment (including moving and improving). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…Ukoha and Beamish found that in Nigeria residents who lived in self-contained houses derived the most satisfaction because of features such as room privacy, toilet, bathroom and playing yard for children. This is in contrast to those living in compound houses, where residents had to share fewer amenities (Konadu-Agyemang 2001b;Sinai 2001). We found that residents in compound houses share toilet, kitchen and bathroom facilities with other occupants, and hence their dissatisfaction with their housing arrangement.…”
Section: Discussioncontrasting
confidence: 70%
“…Ukoha and Beamish found that in Nigeria residents who lived in self-contained houses derived the most satisfaction because of features such as room privacy, toilet, bathroom and playing yard for children. This is in contrast to those living in compound houses, where residents had to share fewer amenities (Konadu-Agyemang 2001b;Sinai 2001). We found that residents in compound houses share toilet, kitchen and bathroom facilities with other occupants, and hence their dissatisfaction with their housing arrangement.…”
Section: Discussioncontrasting
confidence: 70%
“…In the context of housing consumption adjustments, Hhs' reinvestment and mobility decisions are believed to be correlated (Seek, 1983;Shear, 1983;Boehm and Ihlanfeldt, 1986;Potepan, 1989;Montgomery, 1992;Littlewood and Munro, 1997;Baum and Hassan, 1999;Mandič, 2001;Sinai, 2001). The need for adjustments arises when Hhs are faced with a discrepancy between the desired or optimal level of housing consumption and the actual one.…”
Section: Reinvestment Behaviour and Housing Adjustment Optionsmentioning
confidence: 99%
“…The need for adjustments arises when Hhs are faced with a discrepancy between the desired or optimal level of housing consumption and the actual one. For some researchers, Hhs' adjustment options are limited to a simultaneous decision between the discrete alternatives of moving or improving (Shear, 1983;Boehm and Ihlanfeldt, 1986;Potepan, 1989;Montgomery, 1992;Sinai, 2001). For others, moving and improving decisions can be integrated, providing a viable alternative adjustment option to Hhs (Seek, 1983;Littlewood and Munro, 1997;Baum and Hassan, 1999;Mandič, 2001).…”
Section: Reinvestment Behaviour and Housing Adjustment Optionsmentioning
confidence: 99%
“…The house type which provides privacy might be evaluated as a feature that results in satisfaction (Kaitilla, 1993;Ukoha and Beamish, 1997;Baiden et al, 2011). Moreover, the common use of some areas and amenities outside the house might also be seen as a factor of satisfaction in some cases (Konadu, 2001;Sinai, 2001). Ukoha and Beamish (1996) who investigate the effect of different housing types on housing satisfaction in Nigeria not only include modern housing provision types such as apartment, single-family house and single room, but also traditional and cultural ones such as townhouse and bungalow.…”
Section: Literature Review On Housing Satisfactionmentioning
confidence: 99%